Nilai-Nilai Pendidikan Akidah dalam Al-Qur’an - Muhammad Sultan Alfaidz; Wahyu Ariandhika Luthfi; Yasmin Mulya Fadillah Harahap (Young Journal of Social Sciences and Humanities, 2025)
This study aims to examine the educational values of Islamic creed (‘aqīdah) contained in the Qur’an by emphasizing two main dimensions: ‘aqīdah as the foundation of social ethics and as a safeguard for the quality of faith. The study is motivated by the importance of understanding ‘aqīdah in shaping the holistic personality of a Muslim, both in their vertical relationship with Allah and their horizontal relationship with fellow human beings. This research employs a qualitative method using a library research approach, and the data is analyzed through a thematic interpretation (tafsīr maudhū‘ī) of Qur’anic verses related to the core principles of Islamic creed. The findings reveal that the Qur’an does not merely convey theological doctrine in a theoretical sense, but also instills practical educational values. These values include belief in Allah, His messengers, His revealed books, the angels, the Last Day, and divine decree (qadar), which are integrated with social actions such as giving zakat, keeping promises, exercising patience in adversity, and caring for the underprivileged. Thus, ‘aqīdah in the Qur’anic perspective plays a strategic role in shaping both the spiritual and social integrity of a Muslim. This study affirms that religious education in the form of ‘aqīdah not only shapes belief but also directs behavior toward a holistic and transformative religiosity